Chemical composition, structure and properties of glass and glass-ceramic materials in the system of BaO(PbO)-B2O3-Al2O3-TiO2 - Ruiz Valdés, Juan Jacobo; Gorokhovsky, A.; Escalante García, José Iván (Universidad Autónoma de Nuevo León, 2011)
The vitrification and crystallization of glasses in the system BaO(PbO)-B2O3-Al2O3-TiO2.